Longitudinal assessment of anti-SARS-CoV-2 antibody dynamics and clinical features following convalescence from a COVID-19 infection. (June 2021) - Gerhards, Catharina; Thiaucourt, Margot; Kittel, Maximilian; Becker, Celine; Ast, Volker; Hetjens, Michael; Neumaier, Michael; Haselmann, Verena
Highlights: Results show stable anti-SARS-CoV-2 antibody kinetics in a long-term follow-up. Positive correlation between antibody level and disease severity was replicated. Most reported symptoms in the acute stage of COVID-19 disease were anosmia/ageusia. Anosmia/ageusia remained reduced in one-third of participants at long-time follow-up. Abstract: Introduction: The longevity of antibody levels against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the duration of immunity are current topics of major scientific interest. Antibody kinetics during the acute phase are well studied, whereas the long-term kinetics are yet to be determined, with contradictory results from the studies to date. Here, we present a longitudinal analysis of the serological responses to a SARS-CoV-2 infection following convalescence and the association with post-COVID syndrome (PCS). Materials and methods: A total of 237 serum samples were prospectively collected from 61 participants who had had a SARS-CoV-2 infection, which was confirmed using quantitative reverse-transcription polymerase chain reaction (qRT-PCR). For each participant, anti-nucleocapsid (N) and anti-spike subunit 1 receptor binding domain (RBD/S1) immunoglobulin (Ig) levels were regularly determined over a period of 8 months. COVID-19-associated symptoms were assessed using a standardized questionnaire at study entry and again after 6 months. Results: Antibodies were detectable in 56 of the 61 participants. No substantial decline in anti-SARS-CoV-2 pan-Ig levels was observed for the duration of the follow-up period. Antibody levels correlated positively with the disease severity, body mass index, fever, and smoking status. It was found that 46.8% of the participants suffered from PCS, with olfactory and gustatory dysfunctions being the most commonly reported symptoms. Conclusion: The results demonstrate stable anti-SARS-CoV-2 antibody titers and thus may indicate a long-lasting immunity. The results are in line with recently published data and provide further insight concerning asymptomatic to mildly-affected patients, the association with clinical features, and the frequency of PCS.